Effect of Color Variations (Background and Letters) on Current Sources in Running Text P.10 Full Color - Winda Setya; Novia Novia; Muhammad Minan Chusni (UNIVERSITAS INDRAPRASTA PGRI, 2021)
The development and advancement of technology are increasing rapidly, especially in the electronics field to convey information. Running text boards are one of the technologies that are considered efficient to attract the attention of the public in conveying information in public places. The purpose of this study was to determine how the influence of current sources on variations in bacground color and font color variations in running text P.10 full color. This research was conducted by varying 6 color (bacground and letter writing) on the flow. Based on the data obtained, it shows that the color combination shows the number of different currents. The highest current is generated by a white background, especially yellow writing of 4.4 amperes and the lowest current by a black background, especially blue writing of 0.44 amperes.